Pain Over Two Years After Start of Biologic Versus Conventional Combination Treatment in Early Rheumatoid Arthritis: Results From a Swedish Randomized Controlled Trial. Issue 9 (2nd August 2021) - Olofsson, Tor; Wallman, Johan K.; Jöud, Anna; Schelin, Maria E. C.; Ernestam, Sofia; van Vollenhoven, Ronald; Saevarsdottir, Saedis; Lampa, Jon
Abstract : Objective: To compare the pain course between methotrexate (MTX)‐refractory early rheumatoid arthritis (RA) patients randomized to infliximab (IFX) versus sulfasalazine (SSZ) plus hydroxychloroquine (HCQ). Methods: The randomized, controlled, open‐label Swedish Pharmacotherapy (SWEFOT) trial enrolled new‐onset RA patients from October 2002 to December 2005. After 3 months of receiving MTX, patients not reaching low disease activity (Disease Activity Score in 28 joints score ≤3.2) were randomized to adding IFX (n = 128) or SSZ plus HCQ (n = 130) and followed for 21 months. Here, outcomes included area under the curve (AUC) for visual analog scale (VAS) scores for pain, unacceptable pain (VAS pain score >40 mm [range 0–100]), and unacceptable pain despite inflammation control (refractory pain; VAS pain score >40 plus C‐reactive protein level <10 mg/liter). Between‐group differences were analyzed with multivariate regression models. Results: Overall, 50% of randomized patients (n = 258) in the crude setting reported unacceptable pain at randomization, declining to 29% at 21 months ( P < 0.001), when refractory pain constituted 82% of all unacceptable pain. Comparing randomized arms (intent‐to‐treat analysis), the AUC for VAS pain was lower in the MTX plus IFX group ( P = 0.01), and at 21 months, 32% of patients receiving MTX plus IFX and 45% receiving MTX plus SSZ plus HCQ had unacceptable pain (adjusted relative risk 0.68 [95% confidence interval 0.51, 0.90]; P = 0.008). Regarding refractory pain, no between‐group differences were observed. Conclusion: Despite active combination treatment, almost one‐third of new‐onset RA patients reported unacceptable pain after 21 months, and refractory pain constituted more than 4/5 of this pain load. Adding IFX versus SSZ plus HCQ to MTX reduced both cumulative pain and unacceptable pain at 21 months, suggesting less long‐term pain for the biologic therapy. These results display insufficient effects of current treatment strategies on inflammation‐independent pain components, warranting alternative approaches in affected patients.